Apuntes para una historia de Tetuán / Sergio Cardona Herrero, Buenaventura Gómez Ceballos ; (prólogo, Joaquín Arango) - Gómez Ceballos, BuenaventuraArango, Joaquín; Cardona Herrero, Sergio (1961-) (Bibliografía: p. 141)
Datos tomados de la cubierta